Comparison of neutrophil to lymphocyte ratio and prognostic nutritional index with other clinical and molecular biomarkers for prediction of glioblastoma multiforme outcome. - Celine Garrett (Public Library of Science (PLoS), 2021)
Objective Pre- and post-operative neutrophil to lymphocyte ratio (NLR) and prognostic nutritional index (PNI) and other prognostic clinicopathological variables were correlated with progression free survival (PFS) and overall survival (OS) of Glioblastoma Multiforme (GBM) patients. Methods GBM patients (n = 87, single-centre, recruited 2013-2019) were retrospectively divided into low and high groups using literature-derived cut-offs (NLR = 5.07, PNI = 46.97). Kaplan-Meier survival curves and log rank tests assessed PFS and OS. Univariate and multivariate analyses identified PFS and OS prognosticators. Results High vs low post-operative PNI cohort was associated with longer PFS (279 vs 136 days, p = 0.009), but significance was lost on multivariate analysis. Post-operative ECOG (p = 0.043), daily dexamethasone (p = 0.023) and IDH mutation (p = 0.046) were significant on multivariate analysis for PFS. High pre- and post-operative PNI were associated with improved OS (384 vs 114 days, p = 0.034 and 516 vs 245 days, p = 0.001, respectively). Low postoperative NLR correlated with OS (408 vs 249 days, p = 0.029). On multivariate analysis using forward selection process, extent of resection (EOR) (GTR vs biopsy, p = 0.004 and STR vs biopsy, p = 0.011), and any previous surgery (p = 0.014) were independent prognostic biomarkers for OS. On multivariate analysis of these latter variables with literature-derived prognostic biomarkers, EOR remained significantly associated with OS (p = 0.037). Conclusions EOR, followed by having any surgery prior to GBM, are the most significant independent predictors of GBM patient's OS. Post-operative ECOG, daily dexamethasone and IDH mutation are independent prognostic biomarkers for PFS. PNI may be superior to NLR. Post- vs pre-operative serum inflammatory marker levels may be associated with survival.